Study on Fault Diagnosis of Circuit-breaker Based on Rough-Set Theory - Chu Yan; Wang Haiguang; Chen Liang (Institute of Advanced Engineering and Science, 2013)
High voltage circuit-breaker is an important equipment in electric system. The study on fault diagnosis of high voltage circuit-breaker would not only strengthens the security and stability of power system but also increases the economic benefit of it. Obtaining the diagnosis rules is the hardest part in building fault diagnosis expert system. This article analyses the fault samples data of high voltage circuit-breaker by rough set theory, and get diagnosis rules from it. The case shows the method is practical and feasible. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1899